Surgical Management of Postmastectomy Lymphedema and Review of the Literature. Issue 2 (March 2021) - Chen, Kuo; Sinelnikov, Mikhail Y.; Shchedrina, Marina A.; Mu, Lan; Lu, Pengwei
Abstract : Abstract: Upper limb lymphedema is one of the most common complications after breast cancer surgery and radiotherapy. At present, physical methods and surgical methods can be used for treatment. Surgical operations are mainly based on lymphovenous anastomosis and vascularized lymph node transfer. For these 2 surgical methods, we analyzed and compared the literature review and our own clinical experience. We summarized the differences between the 2 surgical techniques and the selection methods. We hope to help more young plastic surgeons and breast doctors understand how to treat upper limb lymphedema through surgical methods and help patients improve their quality of life. Abstract : Supplemental digital content is available in the text.